Thailand - Country Development Partnership : Social Protection - World Bank (Washington, DC, 2013)
The Thailand Country Development Partnership for Social Protection (CDP-SP) is a collaborative program of policy development and technical assistance between the Ministry of Labor and Social Protection and the Bank and was launched in July 2001. CDP-SP operates in three key policy areas: labor markets; social insurance; and social assistance and safety nets. This report reviews the objectives and planning for the three year rolling program, as it was agreed at the launch in July 2001; and highlights the performance of CDP-SP in the first year through June 2002 in five reform areas: social assistance, employment services, unemployment insurance, occupational health and safety, data for social protection. The progress towards achievement of benchmarks is impressive and ahead of schedule in some respects. The formal launch of Year 2 of CDP-SP is anticipated to take place in October/November 2002. Year 2 will involve consolidation of reform into the key steps necessary to improve service performance, the application of technical and analytical insights gained in Year 1, and the preparation of plans for implementing on a larger scale the service improvements that have been agreed.